The Dutch Republic. Laboratory of the Scientific Revolution - Berkel, Klaas van (BMGN - Low Countries Historical Review, 2010)
Historians agree about the significance of the Scientific Revolution for the development of modern society; there is little agreement, however, as to the nature and the causes of this major shift in our perception of the natural world. In this article, it is argued that we may profit from studying this problem in the context of the Dutch Republic during the seventeenth century, the Republic being in many ways a laboratory of modern life. In this article, three factors often mentioned as contributing to the new scientific themes are explored in the Dutch context. The first factor dealt with is the mingling of scholars and craftsmen; the second the role of the universities as centers of both teaching and research, and the third the congruence of scientific and mercantile values in the early modern Dutch trading communities. This article is part of the special issue ’The International Relevance of Dutch History’.